Spazi urbani e pratiche digitali. Verso una nuova forma di azione educativa - Francis, Véronique (Rivista Italiana di Educazione Familiare, 2016)
Urban studies have lately taken into account the “vertical” dimension along with the “horizontal”. But now, with massive advances in mobile digital technologies, especially in the leisure-activities field, it is time to take a closer look at this new dimension in urban space. Based on the findings of a qualitative study of digital strategies institutionally deployed at the level of a town, this article brings out the links between diverse spaces – physical and virtual, material and dematerialized – detailing the use of digital technologies by social and educational institutions. It appears that digital practices generate new forms of professional strategies aimed at the young and their parents. Educational spaces now include digital spaces and have an added ‘reticular’ dimension too.